Gabexate Mesilate (Foy®) as an Anticoagulant in Extracorporeal Circulation in Dogs and Sheep - Oedekoven, B; Bey, R; Mottaghy, K; Schmid-Schönbein, H (Thrombosis and Haemostasis, 1984)
Gabexate mesilate (GM), a synthetic serine protease inhibitor with a short half-life time of approx. 80 sec, was applied as the exclusive anticoagulant in small scale extracorporeal circulation in narcotized dogs and sheep. The animals underwent a veno-venous bypass. As the blood was drawn out of the femoral vein, GM was infused immediately into the extracorporeal system. GM was greatly reduced because of its short half-life time before the blood reentered the animal via a brachial vein. In order to control the coagulatory state of the blood, the Activated Clotting Time (ACT), Partial Thromboplastine Time (PTT) and Recalcification Time (RT) were measured in regular intervals. In addition, a screen pressure test device was used to monitor on line during ECC the tendency of blood clotting. It was shown that the blood of the extracorporeal system was sufficiently anticoagulated by an infusion of 0.03 mg/ml/min GM. During two hours ECC, simultaneously measured ACT - values of the animals only differed up to 10 percent from the native values. Pilot studies have shown that the results of these model investigations could be successfully transferred to extracorporeal circulation with membrane oxygenators and pumps as they are clinically used.
Keywords: Gabexate mesilate; Extracorporeal circulation; Screen pressure